Prognostic factors associated with low back pain outcomes - Gregg CD; McIntosh G; Hall H; Hoffman CW (CSIRO Publishing, 2014)
INTRODUCTION: An improved understanding of prognostic factors associated with low back pain (LBP) outcomes will refine expectations for patients, clinicians and funders alike and improve allocation of health resources to treat the condition. AIM: To establish the link between a range of clinical and sociodemographic prognostic variables for LBP against three separate, clinically relevant outcome measures. METHODS: This was a retrospective, non-experimental study of 1076 consecutive LBP cases treated during a three-year period. Multivariate logistic regression analysis was used to determine the association between potential prognostic variables and outcome measures: clinically relevant reduction in pain, improvement in perceived function, and successful return to work six months after rehabilitation. RESULTS: Patients with clinically relevant improvements in LBP were more likely to have a shorter duration of pain (odds ratio [OR] 1.89), lower baseline pain (OR 1.19), a directional preference for extension activities (OR 1.45) and a history of spine surgery (OR 1.38). Clinically relevant gains in perceived function were observed in patients who were younger (OR 0.98) or those with shorter symptom duration (OR 1.74). Prognostic variables associated with a successful return to work included being female (OR 1.79), having a job available (OR 2.36), intermittent pain (OR 1.48) or a directional preference for extension activities (OR 1.78). DISCUSSION: This study demonstrated that there are a variety of prognostic variables to consider when determining outcome for an individual with LBP. The relative importance of each variable may differ depending on the outcome measured.